2019
DOI: 10.5194/isprs-archives-xlii-3-w8-415-2019
|View full text |Cite
|
Sign up to set email alerts
|

Combining Social Media and Authoritative Data for Crisis Mapping: A Case Study of a Wildfire Reaching Croatian City of Split

Abstract: <p><strong>Abstract.</strong> Due to climate changes, wildfire breakouts get more frequent and difficult to control. In the mid-July 2017, the wildfire spread from wildland to the city of Split, the second-largest city in Croatia. This unpredictable spread almost caused the collapse of emergency response systems. Fortunately, a greater tragedy was avoided with the composure of the responsible services and the help of the citizens. The citizens helped in extinguishing the fire and timely provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…It can also be seen that the distribution was relatively equitable between the two remaining: case study (37.5%) and experiment (26.3%). [29,45,145,181,[190][191][192][193][194][195] It was observed that the most widely used type of DSS continued to be the traditional PDSS (including GIS). Despite technological advances, with the application of AI and Big Data, there is low use of these in the field of forest fires.…”
Section: Rq3mentioning
confidence: 99%
See 1 more Smart Citation
“…It can also be seen that the distribution was relatively equitable between the two remaining: case study (37.5%) and experiment (26.3%). [29,45,145,181,[190][191][192][193][194][195] It was observed that the most widely used type of DSS continued to be the traditional PDSS (including GIS). Despite technological advances, with the application of AI and Big Data, there is low use of these in the field of forest fires.…”
Section: Rq3mentioning
confidence: 99%
“…BA[77,86,90,149,172,[180][181][182][183][184][185][186][187][188][189] Big Data[29,45,145,181,[190][191][192][193][194][195] Figure6. Number of studies found versus the problem to be solved.…”
mentioning
confidence: 99%
“…Proposed approach allows to achieve: -very high accuracy of damage assessment and mapping; -scalability of approach for various emergencies and territories; -ability to work with various combinations of data sources; -low dependency on data quality and quantity; -high automatization and assessment speed ( (Leichter A., et al, 2018, Migliaccio F., et al, 2019, Tavra M., et al, 2019).…”
Section: Introductionmentioning
confidence: 99%